Perioperative Anesthetic Management of Molar Pregnancy Patients with Hyperthyroidism and COVID-19 Underwent Suction Curettage - Bagus Fajar Rochman; Mahendratama Purnama Adhi; Iwan Nuryawan (Majalah Anestesia & Critical Care, 2021)
Background: The incidence of molar pregnancies has increased during the COVID-19 pandemic. Molar pregnancy can cause hyperthyroidism and if not treated immediately can worsen the patient’s condition. A molar pregnancy with hyperthyroidism infected with SARS-CoV-2 poses a challenge for anesthesiologists in perioperative management to prevent complications of thyroid crisis and worsening of COVID-19. Case presentation: A 38-year-old woman was referred to our hospital with a gestational age of 11-12 weeks with vaginal bleeding. Since 2 weeks before being admitted to the hospital the patient complained of fever and the last 3 days had a cough and runny nose. She had no history of contact with COVID-19 patient. On physical examination, her blood pressure was 160/90 mmHg, heart rate was 114 beats per minute, respiratory rate was 18 times per minute, SpO2 was 97% on room air, and body temperature was 37.4oC. Laboratory tests revealed hemoglobin level of 9.2 g/dl, hCG levels > 1,000,000 mIU/ml, and thyroid function tests showed hyperthyroidism. Obstetric ultrasound examination revealed a molar pregnancy. A Burch-Wartofsky score was 20. The real-time transcription-polymerase chain reaction (RT-PCR) test were positive for SARS-CoV-2. In the pre-operative period, the patient was treated with 100 mg of propylthiouracil (PTU) orally every 8 hours and 20 mg of propranolol orally once a day. We performed the curettage suction on the next day under spinal anesthesia using 10 mg of 0.5% hyperbaric bupivacaine. Surgery lasted 75 minutes and performed uneventfully. Evaluation up to 30 days after curettage we found no complications of thyroid crisis and worsening of COVID-19. Conclusion: Innate immune dysregulation due to hyperthyroidism may worsen the clinical course of COVID-19 patients, and conversely, SARS-CoV-2 infection can cause thyroid hormone disorders. Spinal anesthesia can be safely performed in patients with molar pregnancy accompanied by hyperthyroidism and COVID-19